Perkawinan Sebagai Konstruksi Dasar Hubungan Kekerabatan Dan Tanggung Jawab Seorang Laki-Laki Terhadap Anak Di Indonesia - Rifaldi Adi Tama; Umar Haris Sanjaya (Fakultas Hukum Universitas Islam Indonesia, 2023)
In theory, the Constitutional Court Decision Number 46/PUU-VIII/2010 regarding the review of the Marriage Law stipulates the definition of a child out of wedlock as a child from unregistered marriage. However, in practice there is a fact that there is a lawsuit from the mother of a child resulting from a non-marital relationship contained in the decision of the Tangerang District Court No. 746/Pdt.G/2021/PN.Tng. rejected due to the absence of marriage between the parties. The formulation of the problem in this study is: How can a man be related to kinship and responsibility with children in Indonesia?; and Can kinship relations and responsibilities between men and children arise without marriage relations in Indonesia? This research is a normative legal research with a statute approach as well as a conceptual approach and a case approach regarding marriage as the basis of kinship relations and the responsibility of a man towards children in Indonesia. The results of this study indicate that marriage and blood relations (nasab) are elements that must be fulfilled to link kinship and responsibilities between men and children. Without the fulfillment of these elements, the child cannot be related to his kinship and responsibilities with a man. The conclusion shows that the marital relationship is an important element to link kinship and bind men's responsibilities with a child. On this matter, the author suggests to the Court to reject the application that is about responsibility for children resulting from non-marital relations and a man can be given a ta'zir if it can be proven first that he has a blood relationship with a child from non-marital relationship.